A federated simulation method for multi-modal transportation systems: combining a discrete event-based logistics simulator and a discrete time-step-based traffic microsimulator. (February 2015) - Wall, Thomas A; Rodgers, Michael O; Fujimoto, Richard; Hunter, Michael P
The primary focus of computer simulation in transportation engineering has been to model individual systems using modeling software packages designed for the specific system under investigation. However, this limits the ability to explore interactions between multiple disparate transportation systems in a dynamic modeling environment. To address this gap, this study develops and tests a technique to federate two transportation models, each constructed using different simulation software packages: (1) a discrete event-based simulation model of a freight trucking terminal and (2) a discrete time-step-based traffic microscopic simulation model of the network serving the terminal. The federation technique is tested to consider potential feedback loops that may arise between the models during a single simulation run. It is then applied in a notional case study of the Port of Savannah to further assess its capabilities. The findings suggest that this federated simulation technique captures the dynamic interaction of the two systems being modeled. A comparison of the observed versus expected time-based characteristics of the interactions are shown to yield statistically significant correlation.